Route map, Juneau to Porcupine River, Alaska / U.S. Cost and Geodetic Survey (Washington, D.C. : U.S. Coast and Geodetic Survey, 1898)
Relief shown by hachures and spot heights.; Oriented with north toward upper right.; "U.S.C. & G.S. 3100." Color; 1:1,200,000